Distinct Motifs in ATAD5 C-Terminal Domain Modulate PCNA Unloading Process - Eunjin Ryu; Na Young Ha; Woojae Jung; Juyeong Yoo; Kyungjae Myung; Sukhyun Kang (Cells, 2022)
Proliferating cell nuclear antigen (PCNA) is a DNA clamp that functions in key roles for DNA replication and repair. After the completion of DNA synthesis, PCNA should be unloaded from DNA in a timely way. The ATAD5-RFC-Like Complex (ATAD5-RLC) unloads PCNA from DNA. However, the mechanism of the PCNA-unloading process remains unclear. In this study, we determined the minimal PCNA-unloading domain (ULD) of ATAD5. We identified several motifs in the ATAD5 ULD that are essential in the PCNA-unloading process. The C-terminus of ULD is required for the stable association of RFC2-5 for active RLC formation. The N-terminus of ULD participates in the opening of the PCNA ring. ATAD5-RLC was more robustly bound to open-liable PCNA compared to the wild type. These results suggest that distinct motifs of the ATAD5 ULD participate in each step of the PCNA-unloading process.